1993
DOI: 10.1111/j.1365-2249.1993.tb07965.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of soluble CD21 as a parameter of B cell activation

Abstract: SUMMARYIn this study we established a novel solid-phase immunoassay for CD21 using the time-resolved tluoresccnccof lanthanidechclates. The capture assay was able to detect concentrations ofas low as IOOpgofCD2l antigen per millil[trcor.saniple and was used for quantitative determination orCD21 in lysatcs of different cell lines as well as in patient serum specimens. CD21 was measured in lysates of tonsils and eell lines of B, T cell and myelomonoeyte lineage, and appeared to eonsist ofmonomeric aniigen under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…As the interesting investigation by Huemer et al shows, increased amounts of sCR2 are found in the serum of patients with infectious mononueleosis and rubella, two diseases due to lymphotropic viruses and associated with a marked lymphoproliferation [32]. It was also confirmed that raised serum levels of sCR2 are found in B cell chronic lymphocytic leukaemia.…”
Section: "4mentioning
confidence: 80%
See 1 more Smart Citation
“…As the interesting investigation by Huemer et al shows, increased amounts of sCR2 are found in the serum of patients with infectious mononueleosis and rubella, two diseases due to lymphotropic viruses and associated with a marked lymphoproliferation [32]. It was also confirmed that raised serum levels of sCR2 are found in B cell chronic lymphocytic leukaemia.…”
Section: "4mentioning
confidence: 80%
“…In this issue Huemer et at. describe an ingenious new antigen-capture/fluorescent chelate assay for sCR2 whieh detects concentrations of monomeric antigen as low as 0-1 ng/ml [32]. They find a discrepancy in the absolute values of sCR2 obtained by their technique compared with reported HA results.…”
Section: "4mentioning
confidence: 97%
“…In B lymphocytes, CD21 ampliWes the signal through the B-cell receptor [14], and in turn, B-cell receptor activation induces CD21 shedding [15]. The clinical signiWcance of sCD21 is shown by higher levels in sera of patients with EBV infection and lymphoblastoid tumors [16] and lower levels in autoimmune diseases like RA, SLE, Sjoegren's syndrome, and antiphospholipid syndrome [15,[17][18][19][20]. sCD21 activates monocytes through binding to membrane CD23 and leads to degranulation of basophils upon crosslinking [21].…”
Section: Introductionmentioning
confidence: 99%
“…This complex amplifies the signal transmitted through the B-cell receptor by specific antigen and thereby reduces the threshold of antigen necessary to initiate cell proliferation [6,7]. CD21 is shed from the surface of the cell and is found circulating in plasma [8][9][10]. Soluble CD21 (sCD21) activates monocytes through binding to membrane CD23.…”
Section: Introductionmentioning
confidence: 99%